A flame retardant PC composite material and preparation method thereof

Through silane coupling agent-modified glass fiber and hexachlorocyclic triphosphazene polymer grafting technology, combined with nano concave and convex rod soil and PBT, the flame retardant performance and fluidity problems of PC/ABS composite materials are solved, significantly improving the machinery Performance and flame retardant effect ensure the uniformity and stability of the composite material.

CN118638404BActive Publication Date: 2024-12-31BANSHING PLASTICS PROD SHANGHAI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411103041.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-31
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The oxygen index of PC/ABS composites is low, the flame retardant performance is poor, and the addition of flame retardant and glass fibers can easily affect the fluidity and mechanical properties, and there is a problem of uneven dispersion.

Method used

Using glass fiber and nano-concave and concave rod soil modified with silane coupling agent, as well as hexachlorocyclic triphosphazene polymer grafting technology, the flame retardant layer and enhanced network structure are formed, and the compatibility of glass fibers and composite materials is improved. and flame retardant effect, and improve fluidity through the addition of PBT.

Benefits of technology

The mechanical properties, flame retardant properties and flowability of the composite material are significantly improved, ensuring the uniformity and mechanical strength of the flame retardant effect, while suppressing the wick effect of glass fibers, improving the appearance and overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and specifically discloses a flame-retardant PC composite material and a preparation method thereof. The flame-retardant PC composite material comprises the following substances in parts by weight: 50‑80 parts of PC; 20‑50 parts of ABS; 10‑20 parts of glass fiber; 5‑10 parts of filler; 1‑10 parts of flame retardant; 0.5 parts of antioxidant; 2‑10 parts of flow agent; 0.5 parts of weathering agent; the glass fiber is glass fiber modified with a silane coupling agent. The preparation method thereof is: S1, drying of raw materials; S2, treatment of glass fiber and filler; S3, preparation of composite materials. The composite material of the present application can be used in the fields of automotive parts, household appliances, etc., and has the advantages of excellent flame retardancy and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of PC composite materials, and more specifically, to a flame retardant PC composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a thermoplastic engineering plastic with excellent comprehensive performance. It has outstanding impact resistance, excellent mechanical properties and flame retardancy. However, it has disadvantages such as high melt viscosity, poor processing fluidity and poor solvent resistance when used alone. It usually needs to be compounded with other materials. Common PC composite materials include PC / ABS composite materials, which combine the excellent properties of the two materials and can be widely used in automotive interior parts, business machines, communication equipment, household appliances and lighting equipment.

[0003] However, the oxygen index of PC / ABS composite materials is low, that is, the flame retardant performance of the composite materials is poor. It is necessary to add flame retardants and fillers with heat-resistant and flame-retardant effects to the composite materials to improve the flame retardant performance and temperature sensitivity of the composite materials. However, the addition of flame retardants and glass fibers can easily affect the fluidity of the composite materials, and there is a problem of uneven dispersion, which affects the mechanical properties and flame retardant uniformity of the composite materials. Summary of the invention

[0004] In order to improve the mechanical properties and flame retardant properties of the composite material, the present application provides a flame retardant PC composite material and a preparation method thereof.

[0005] The present application provides a flame retardant PC composite material, which adopts the following technical solution:

[0006] In a first aspect, the present application provides a flame retardant PC composite material, comprising the following substances in parts by weight:

[0007] PC50-80 copies;

[0008] ABS 20-50 copies;

[0009] Glass fiber 10-20 parts;

[0010] 5-10 parts of filler;

[0011] Flame retardant 1-10 parts;

[0012] 0.5 parts of antioxidant;

[0013] 2-10 parts of flowing agent;

[0014] 0.5 parts of weathering agent; the glass fiber is glass fiber modified by silane coupling agent.

[0015] By adopting the above technical solution, the PC and ABS composite material has better processing performance, impact toughness and temperature resistance. Glass fibers can be interwoven in the composite material to form a mesh connection. Due to the better heat resistance of the glass fibers themselves, a heat-resistant reinforced network structure can be introduced into the composite material, which can effectively improve the mechanical properties of the composite material. The glass fibers are modified by a silane coupling agent, and the silane coupling agent can be combined with the glass fibers through hydrogen bonds to reduce the surface polarity of the glass fibers, thereby reducing the possibility of glass fiber agglomeration. At the same time, the roughness of the glass fiber surface is increased, the bonding effect between the glass fiber and the composite material is improved, and the possibility of the glass fiber floating to the surface of the composite material can be suppressed, so that the composite material has a better appearance.

[0016] Optionally, the glass fiber is grafted with a hexachlorocyclotriphosphazene polymer.

[0017] By adopting the above technical solution, the hexachlorocyclotriphosphazene polymer has a relatively active P-Cl, which can be grafted on the surface of the glass fiber to form a PN-Si synergistic flame retardant effect with the glass fiber, and can simultaneously exert the condensed phase and gas phase flame retardant effects, and can effectively improve the flame retardant effect of the composite material. In addition, through the grafting of the hexachlorocyclotriphosphazene polymer, a thick flame retardant layer is formed on the surface of the glass fiber, which can increase the roughness of the surface of the glass fiber, not only improve the compatibility and bonding effect of the glass fiber and the composite material, but also reduce the surface wetting and adsorption capacity of the glass fiber, slow down the combustion speed, and inhibit the candle wick effect brought by the glass fiber, thereby further improving the flame retardant effect of the composite material.

[0018] Optionally, the preparation method of the glass fiber is as follows:

[0019] S1. Preparation of silane-modified glass fiber: immersing the glass fiber in acetone, condensing and refluxing, and drying to obtain purified glass fiber; immersing the glass fiber in a silane coupling agent solution, condensing and refluxing, filtering, washing, and drying to obtain silane-modified glass fiber;

[0020] S2. Preparation of hexachlorocyclotriphosphazene polymer: tetrahydrofuran, hexachlorocyclotriphosphazene, m-phenylenediamine and triethylamine are taken respectively, tetrahydrofuran, hexachlorocyclotriphosphazene and m-phenylenediamine are mixed, stirred until dissolved to obtain a mixed solution, triethylamine is added to the mixed solution, stirred at a constant temperature, reacted continuously, cooled, washed and dried to obtain a hexachlorocyclotriphosphazene polymer;

[0021] S3. Preparation example of graft modified glass fiber: Silane modified glass fiber, tetrahydrofuran, hexachlorocyclotriphosphazene polymer and triethylamine are mixed, refluxed under nitrogen protection, cooled, filtered, washed and dried to obtain graft modified glass fiber.

[0022] By adopting the above technical scheme, the preparation method of glass fiber is optimized, hexachlorocyclotriphosphazene and metaphenylenediamine undergo nucleophilic substitution to form hyperbranched polymers, and the amino groups of the hyperbranched polymers combine with the epoxy groups between the silane-modified glass fibers to complete the grafting of the hyperbranched polymers on the surface of the glass fibers, so that an inert and rough flame retardant layer is formed on the surface of the glass fibers, effectively inhibiting the candle wick effect of the glass fibers. The hyperbranched polymers have a three-dimensional structure, molecular chains that are not easily entangled, and highly active end groups, so that a reactive interface is formed between the hyperbranched polymers and the composite materials, thereby further improving the compatibility between the glass fibers and the composite materials, and synergistically improving the mechanical properties and flame retardant properties of the composite materials.

[0023] Optionally, the length of the glass fiber is 1-3 mm.

[0024] By adopting the above technical solution, the length of the glass fiber is optimized, and glass fibers of appropriate length can be interwoven to form a network structure and are not prone to agglomeration. A uniformly dispersed glass fiber network can be formed in the composite material, so that the composite material has uniform mechanical strength and heat resistance.

[0025] Optionally, the filler includes nano-attapulgite.

[0026] By adopting the above technical solution, nano-attapulgite not only has better rigidity but also has excellent high temperature resistance. Using nano-attapulgite as a filler can effectively improve the mechanical properties, high temperature resistance, wear resistance and flame retardant effects of the composite material.

[0027] Optionally, the nano attapulgite is nano attapulgite modified with a silane coupling agent.

[0028] By adopting the above technical scheme, the silane coupling agent can combine with the hydroxyl group on the nano-attapulgite after hydrolysis, introduce active groups on the nano-attapulgite, reduce the surface polarity of the nano-attapulgite, and enhance the interface interaction between the nano-attapulgite and the composite material, so that the nano-attapulgite is evenly dispersed and filled in the composite material, and the composite material obtains uniform mechanical strength and flame retardant effect.

[0029] Optionally, the filler also includes graphene oxide.

[0030] By adopting the above technical solution, graphene oxide has a two-dimensional honeycomb structure formed by a single layer of carbon atoms arranged in an sp2 hybrid manner, which can introduce a unique layer structure into the composite material to enhance the mechanical properties of the composite material, and can form a shielding layer in the composite material through a barrier effect, which can effectively improve the flame retardant effect of the composite material. The edges of the graphene oxide layer contain more oxygen-containing groups, which can not only be evenly dispersed in the composite material, but also have a strong interaction with the other components in the filler, which can drive the filler to be evenly dispersed in the composite material, so that the composite material obtains uniform mechanical strength.

[0031] Optionally, the nano-attapulgite is loaded on the graphene oxide, and the specific preparation method is as follows: dispersing the silane-modified nano-attapulgite in water to obtain a dispersion, dispersing the graphene oxide in water to obtain a graphene solution, mixing the dispersion and the graphene solution, ultrasonically treating, standing, washing, and freeze-drying to obtain a product.

[0032] By adopting the above technical scheme, amino groups are grafted onto the silane-modified nano-attapulgite, and the amino groups are combined with the oxygen-containing groups at the edges of the graphene oxide sheets by electrostatic assembly, so that the nano-attapulgite is loaded on the surface of the graphene oxide sheet structure, reducing the possibility of attapulgite agglomeration, allowing the filler to be evenly dispersed in the composite material, and the composite material obtains uniform flame retardant effect and mechanical strength.

[0033] Optionally, the flow agent includes PBT.

[0034] By adopting the above technical scheme, a ternary blend system can be formed in the composite material by adding PBT, an ester exchange can occur between PC and PBT, and a coated or adhered ternary morphological structure can be formed during the melting process, thereby effectively enhancing the compatibility between PC and ABS in the composite material. In addition, since PBT itself has better fluidity, the overall fluidity of the composite material is effectively improved, so that the filler and glass fiber can be evenly dispersed in the composite material to form a filler network, thereby improving the mechanical strength and flame retardant effect of the composite material.

[0035] In a second aspect, the present application provides a method for preparing a flame retardant PC composite material, using the following technical solution:

[0036] A method for preparing a flame retardant PC composite material comprises the following steps:

[0037] S1. Raw material drying: PC and ABS are dried separately to obtain dry PC and dry ABS;

[0038] S2, glass fiber and filler treatment: glass fiber and 1 / 2 weight part of filler are taken respectively by weight, the filler is dispersed in DMF to obtain a dispersion, the glass fiber is immersed in the dispersion, a condensation agent is added, stirred, filtered, washed, and dried to obtain a glass fiber-filler mixture;

[0039] S3, preparation of composite materials: dry PC, dry ABS, 1 / 2 weight part of filler, flame retardant, antioxidant, flow agent and weathering agent are mixed at high speed to obtain a mixture, and the mixture and the glass fiber-filler mixture obtained in step S2 are placed in an extruder, melt-extruded, granulated, cooled and dried to obtain a composite material.

[0040] By adopting the above technical scheme, preferably pre-treating the glass fiber and part of the filler, the filler can be loaded on the glass fiber under the initiation of the condensation agent, thereby forming a micro-nano hierarchical structure of attapulgite, graphene oxide and glass fiber, which can further reduce the possibility of glass fiber agglomeration, enable the glass fiber to stably form an enhanced flame retardant network in the composite material, and improve the mechanical properties and flame retardant effect of the composite material.

[0041] In summary, this application has the following beneficial effects:

[0042] 1. Since the glass fibers in the present application can be interwoven in the composite material to form a mesh connection, and since the glass fibers themselves have good heat resistance, a heat-resistant enhanced network structure can be introduced into the composite material, which can effectively improve the mechanical properties of the composite material. The glass fibers are modified by a silane coupling agent, and the silane coupling agent can be combined with the glass fibers through hydrogen bonds to reduce the surface polarity of the glass fibers, thereby reducing the possibility of glass fiber agglomeration. At the same time, the roughness of the glass fiber surface is increased, the bonding effect between the glass fiber and the composite material is improved, and the possibility of the glass fiber floating to the surface of the composite material can be suppressed, so that the composite material has a better appearance.

[0043] 2. In the present application, hexachlorocyclotriphosphazene and m-phenylenediamine undergo nucleophilic substitution to form a hyperbranched polymer, which is grafted onto glass fiber to form an inert and rough flame-retardant layer on the surface of the glass fiber, effectively inhibiting the wick effect of the glass fiber. The hyperbranched polymer has a three-dimensional structure, a molecular chain that is not easily entangled, and a highly active end group, so that a reactive interface is formed between the hyperbranched polymer and the composite material, thereby further improving the compatibility between the glass fiber and the composite material, and synergistically improving the mechanical properties and flame retardant properties of the composite material.

[0044] 3. In the present application, amino groups are grafted onto the silane-modified nano-attapulgite, and the amino groups are combined with the oxygen-containing groups at the edges of the graphene oxide sheets by electrostatic assembly, so that the nano-attapulgite is loaded on the surface of the graphene oxide sheet structure, reducing the possibility of attapulgite agglomeration, allowing the filler to be evenly dispersed in the composite material, and the composite material obtains uniform flame retardant effect and mechanical strength. DETAILED DESCRIPTION

[0045] The present application is further described in detail below with reference to the embodiments.

[0046] Preparation Example

[0047] In the preparation examples of this application, the selected drugs are as follows, but not limited to them:

[0048] Glass fiber: 3mm chopped glass fiber from Taian Haosong Fiber Co., Ltd.

[0049] Acetone: Sinopharm Chemical Reagent Co., Ltd., analytical grade;

[0050] Silane coupling agent: Silane coupling agent KH550 from Nanjing Pinyoudao Chemical Technology Co., Ltd.

[0051] Tetrahydrofuran: Sinopharm Chemical Reagent Co., Ltd., analytical grade;

[0052] Triethylamine: Sinopharm Chemical Reagent Co., Ltd., analytical grade;

[0053] m-phenylenediamine: MacLean, analytical grade;

[0054] Hexachlorocyclotriphosphazene: MacLean, analytical grade;

[0055] Attapulgite: Changzhou Jefferson New Material Technology Co., Ltd., the specification is 99.9% nano-attapulgite;

[0056] Ethanol: MacLean, analytical grade;

[0057] Acetic acid: Maclean, analytical grade;

[0058] Graphene oxide: Single-layer graphene oxide from Jiangsu Toyotai Carbon Products Co., Ltd.

[0059] Glass fiber preparation example

[0060] Preparation Example 1

[0061] 50 g of glass fiber was immersed in acetone, condensed and refluxed at 70°C for 2 hours, filtered, and dried at 80°C for 24 hours to obtain purified glass fiber; the glass fiber was immersed in a 2% by mass silane coupling agent KH550 solution, condensed and refluxed at 80°C, filtered, washed, and dried at 120°C for 12 hours to obtain silane-modified glass fiber.

[0062] Preparation Example 2

[0063] The preparation method of glass fiber is as follows:

[0064] S1. Preparation of silane-modified glass fiber: 50 g of glass fiber was immersed in acetone, condensed and refluxed at 70°C for 2 h, filtered, and dried at 80°C for 24 h to obtain purified glass fiber; the glass fiber was immersed in a 2% by mass silane coupling agent KH550 solution, condensed and refluxed at 80°C, filtered, washed, and dried at 120°C for 12 h to obtain silane-modified glass fiber;

[0065] S2. Preparation of hexachlorocyclotriphosphazene polymer: 100 mL of tetrahydrofuran, 2.5132 g of hexachlorocyclotriphosphazene, 4.6713 g of m-phenylenediamine and 4.3612 g of triethylamine were taken respectively, tetrahydrofuran, hexachlorocyclotriphosphazene and m-phenylenediamine were mixed, and stirred under a nitrogen atmosphere until dissolved to obtain a mixed solution, triethylamine was added to the mixed solution, and the mixture was stirred at a constant temperature of 70° C. for 12 h, the reaction was continued, and the mixture was cooled, washed, and dried at 45° C. for 8 h to obtain a hexachlorocyclotriphosphazene polymer;

[0066] S3. Preparation example of graft modified glass fiber: 5 g of silane modified glass fiber, 150 mL of tetrahydrofuran, 3.4534 g of hexachlorocyclotriphosphazene polymer and 1.5 mL of triethylamine are mixed, refluxed under nitrogen protection, cooled, filtered, washed and dried to obtain graft modified glass fiber.

[0067] Attapulgite Preparation Example

[0068] Preparation Example 3

[0069] 2g of attapulgite was added to a mixed solution of 150ml of ethanol / deionized water, and dispersed by ultrasonication for 30min, wherein the volume ratio of ethanol to deionized water in the mixed solution was 3:1. Silane coupling agent KH550 was hydrolyzed in an acetic acid aqueous solution with a pH of 3 for 30min, and then added to a mixed solution of ethanol / deionized water, and reacted at 70°C for 24h. After the reaction, the product was centrifuged and separated, and the product was washed 3 times with a mixed solution of ethanol / deionized water, and dried at 110°C for 10h to obtain modified attapulgite.

[0070] Preparation example of nano-attapulgite loaded on graphene oxide

[0071] Preparation Example 4

[0072] 9 g of silane-modified nano-attapulgite was dispersed in 1800 mL of water to obtain a dispersion, 1 g of graphene oxide was dispersed in 500 mL of water to obtain a graphene solution, the dispersion was mixed with the graphene solution, ultrasonically treated for 1 h, allowed to stand for 12 h, the precipitate was washed 3 times, and freeze-dried to obtain a product.

[0073] Example

[0074] Examples 1-3

[0075] On the one hand, the present application provides a flame retardant PC composite material, including PC, ABS, glass fiber, filler, flame retardant, antioxidant, flow agent and weathering agent, and the specific quality is shown in the table below.

[0076] Among them, PC: brand PC-7020PJ, melt flow rate of 16g / 10min, ABS: brand ABS-8391, melt flow rate of 7.9g / 10min, glass fiber is the glass fiber prepared in Preparation Example 1, the length of the glass fiber is 3mm, the filler is 1800 mesh nano-attapulgite, the flame retardant is TPP, the antioxidant is antioxidant 1010, the flow agent: PBT with a melt mass flow rate of 16g / 10min, and the weathering agent is ultraviolet absorber UV351.

[0077] On the other hand, the present application provides a method for preparing a flame retardant PC composite material, comprising the following steps:

[0078] S1. Raw material drying: PC is dried at 110°C for 4 hours, and ABS is dried at 90°C for 4 hours to obtain dry PC and dry ABS;

[0079] S2. Treatment of glass fiber and filler: glass fiber and 1 / 2 weight part of filler are taken respectively by weight, the filler is dispersed in DMF to obtain a dispersion with a mass fraction of 2%, the glass fiber is immersed in the dispersion, a condensation agent HATU (tetramethyluronium hexafluorophosphate) is added, stirred, filtered, washed, and dried to obtain a glass fiber-filler mixture;

[0080] S3. Preparation of composite materials: PC, ABS, 1 / 2 parts by weight of filler, flame retardant, antioxidant, flow agent and weathering agent are mixed at high speed to obtain a mixture, and the mixture and the glass fiber-filler mixture obtained in step S2 are placed in an extruder, melt-extruded, granulated, cooled and dried to obtain a composite material.

[0081] Table 1 Composition of composite materials of Examples 1-3

[0082]

[0083] Example 4

[0084] The difference from Example 3 is that the glass fiber prepared in Preparation Example 2 with the same mass and a length of 3 mm is used to replace the glass fiber in Example 3.

[0085] Example 5

[0086] The difference from Example 3 is that the glass fiber prepared in Preparation Example 2 with the same mass and a length of 1 mm is used to replace the glass fiber in Example 3.

[0087] Example 6

[0088] The difference from Example 3 is that an equal mass of the nano attapulgite prepared in Preparation Example 3 is used as filler to replace the nano attapulgite in Example 1.

[0089] Example 7

[0090] The difference from Example 3 is that the filler includes nano-attapulgite and graphene oxide in a mass ratio of 9:1.

[0091] Example 8

[0092] The difference from Example 3 is that an equal mass of the product prepared in Preparation Example 4 is used to replace the nano-attapulgite in Example 1 as a filler.

[0093] Comparative Example

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 3 is that the glass fiber in this comparative example is not modified by a silane coupling agent.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 3 is that the filler in this comparative example is graphene oxide.

[0098] Performance testing

[0099] (1) Tensile strength test: According to GB / T1040-2006, the tensile properties of the samples were tested using an electronic universal material testing machine; the tensile rate was 10 mm / min.

[0100] (2) Flame retardant performance test: The mixed composite material sample was placed in a flat vulcanizer for hot pressing and cooling to prepare a 1.6 mm thick sheet. The prepared sheet was cut into standard specimens of 125 mm × 12.5 mm × 1.6 mm using a universal test cutting machine, and the specimens were subjected to a vertical combustion test according to UL94-V0 in the GB / T2408-2021 standard.

[0101] (3) Impact strength test: The formed 4 mm thick composite material sheet was cut into standard impact specimens of 100 mm × 10 mm × 4 mm using a universal test cutting machine. The impact performance of the impact specimens was tested according to GB / T1843-2008 standard, with a notch depth of 2 mm.

[0102] Table 2 Performance test

[0103]

[0104] Combining the performance test comparison in Table 2, we can find that:

[0105] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the mechanical properties and flame retardant properties of the composite materials prepared in Examples 1-3 are improved, which shows that the flame retardant TPP used in the present application in combination with nano-attapulgite can play a gas phase flame retardant effect and a condensed phase flame retardant effect, and synergistically improve the flame retardant effect of the composite material. And the appropriate amount of flame retardant added can effectively improve the flame retardant effect of the composite material. The glass fiber is modified by a silane coupling agent, and the silane coupling agent can be combined with the glass fiber through hydrogen bonds to reduce the surface polarity of the glass fiber, thereby reducing the possibility of glass fiber agglomeration. At the same time, the roughness of the glass fiber surface is increased, the bonding effect between the glass fiber and the composite material is improved, and the possibility of the glass fiber floating to the surface of the composite material can be suppressed, so that the composite material has a better appearance.

[0106] 2. By comparing Examples 4-5 with Example 3, it can be found that the mechanical properties and flame retardant properties of the composite materials prepared in Examples 4-5 are improved, which indicates that the hexachlorocyclotriphosphazene hyperbranched polymer is grafted on the glass fiber in the present application, so that an inert and rough flame retardant layer is formed on the surface of the glass fiber, which effectively inhibits the candle wick effect of the glass fiber. In addition, the hyperbranched polymer has a three-dimensional structure, a molecular chain that is not easily entangled, and a highly active end group, so that a reactive interface is formed between the hyperbranched polymer and the composite material, thereby further improving the compatibility between the glass fiber and the composite material, and synergistically improving the mechanical properties and flame retardant properties of the composite material.

[0107] 3. By comparing Example 6 with Example 3, it can be found that the mechanical properties and flame retardant properties of the composite material prepared in Example 6 are improved, which shows that the silane coupling agent used in this application can combine with the hydroxyl group on the nano-attapulgite after hydrolysis, introduce active groups on the nano-attapulgite, reduce the surface polarity of the nano-attapulgite, and enhance the interface interaction between the nano-attapulgite and the composite material, so that the nano-attapulgite is evenly dispersed and filled in the composite material, and the composite material obtains uniform mechanical strength and flame retardant effect. It can be seen from the impact strength that the modified nano-attapulgite can be evenly dispersed and improve the impact resistance of the composite material.

[0108] 4. By comparing Examples 7-8 with Example 3, it can be found that the mechanical properties and flame retardant properties of the composite materials prepared in Examples 7-8 are improved, which indicates that the edges of the graphene oxide sheets in the present application contain more oxygen-containing groups, which can not only be evenly dispersed in the composite material, but also have a strong interaction with the other components in the filler, which can drive the filler to be evenly dispersed in the composite material, so that the composite material obtains uniform mechanical strength.

[0109] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flame retardant PC composite material, characterized in that: The following materials are included in parts by weight: Polycarbonate PC 50-80 parts; Acrylonitrile-styrene-butadiene copolymer ABS 20-50 parts; Glass fiber 10-20 parts; 8-10 parts of filler; Flame retardant 1-10 parts; 0.5 parts of antioxidant; 2-10 parts of flowing agent; 0.5 parts of weathering agent; the glass fiber is glass fiber modified by silane coupling agent; The filler includes nano-attapulgite; The glass fiber is grafted with a hexachlorocyclotriphosphazene polymer; The preparation method of the glass fiber is as follows: S1. Preparation of silane-modified glass fiber: immersing the glass fiber in acetone, condensing and refluxing, and drying to obtain purified glass fiber; immersing the glass fiber in a silane coupling agent solution, condensing and refluxing, filtering, washing, and drying to obtain silane-modified glass fiber; S2. Preparation of hexachlorocyclotriphosphazene polymer: tetrahydrofuran, hexachlorocyclotriphosphazene, m-phenylenediamine and triethylamine are taken respectively, tetrahydrofuran, hexachlorocyclotriphosphazene and m-phenylenediamine are mixed, and stirred until dissolved to obtain a mixed solution, triethylamine is added to the mixed solution, stirred at a constant temperature, reacted continuously, cooled, washed, and dried to obtain a hexachlorocyclotriphosphazene polymer; S3. Preparation example of graft modified glass fiber: silane modified glass fiber, tetrahydrofuran, hexachlorocyclotriphosphazene polymer and triethylamine are mixed, refluxed under nitrogen protection, cooled, filtered, washed and dried to obtain graft modified glass fiber; The length of the glass fiber is 1-3 mm; The glass fiber and the filler are treated by taking the glass fiber and 1 / 2 weight part of the filler respectively by weight, dispersing the filler in DMF to obtain a dispersion, immersing the glass fiber in the dispersion, adding a condensation agent, stirring, filtering, washing, and drying to obtain a glass fiber-filler mixture.

2. The flame retardant PC composite material according to claim 1, characterized in that: The nano attapulgite is nano attapulgite modified by a silane coupling agent.

3. The flame retardant PC composite material according to claim 1, characterized in that: The filler also includes graphene oxide.

4. The flame retardant PC composite material according to claim 3, characterized in that: The nano-attapulgite is loaded on the graphene oxide, and the specific preparation method is as follows: dispersing the silane-modified nano-attapulgite in water to obtain a dispersion, dispersing the graphene oxide in water to obtain a graphene solution, mixing the dispersion with the graphene solution, ultrasonically treating, standing, washing, and freeze-drying to obtain a product.

5. The flame retardant PC composite material according to claim 1, characterized in that: The flow agent includes PBT.

6. The method for preparing a flame retardant PC composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Raw material drying: PC and ABS are dried separately to obtain dry PC and dry ABS; S2, glass fiber and filler treatment: glass fiber and 1 / 2 weight part of filler are taken respectively by weight, the filler is dispersed in DMF to obtain a dispersion, the glass fiber is immersed in the dispersion, a condensation agent is added, stirred, filtered, washed, and dried to obtain a glass fiber-filler mixture; S3, preparation of composite materials: dry PC, dry ABS, 1 / 2 weight part of filler, flame retardant, antioxidant, flow agent and weathering agent are mixed at high speed to obtain a mixture, and the mixture and the glass fiber-filler mixture obtained in step S2 are placed in an extruder, melt-extruded, granulated, cooled and dried to obtain a composite material.

Citation Information

Patent Citations

  • Intumescent flame-retardant reinforced PC (Polycarbonate) / ABS (Acrylonitrile Butadiene Styrene) alloy and preparation method thereof

    CN103951959A

  • Long glass fiber reinforced flame-retardant ABS composite material and preparation method thereof

    CN112011147A

  • PVC (Polyvinyl Chloride) guardrail material for highway and preparation method of PVC guardrail material

    CN118146599A

  • Preparation process of glass fiber composite material reinforced modified PET (Polyethylene Terephthalate) material

    CN118165316A

  • Flame retardant polymeric compositions containing halogen substituted hexakis-(substituted phenoxy)cyclotriphosphazene

    US4029634A